AN ANALYTICAL APPROACH TO BUILDING A TECHNOLOGY DEVELOPMENT ENVELOPE (TDE) FOR ROADMAPPING OF EMERGING TECHNOLOGIES - GERDSRI, N. (International Journal of Innovation and Technology Management (IJITM), 2007)
This paper presents the research on the development of a new concept and methodology called Technology Development Envelope (TDE). The TDE approach is applied to identify the optimum path in developing a technology roadmap in which the company's technology strategies and business strategies are combined. TDE allows the executive level decision makers in corporations, as well as the policy level decision makers in governments to incorporate emerging technologies into the development of technology strategies. The combination of Delphi method and Hierarchical Decision Modeling (HDM) is used as a foundation for building the TDE concept. The judgments from technology developers and technology implementers are utilized in the process to ensure that the technology strategies are in full support of corporate goals and objectives.